2001
DOI: 10.1124/mol.59.5.1171
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Multidrug Resistance Protein 1 (MRP1/ABCC1) Transport and ATPase Activities by Interaction with Dietary Flavonoids

Abstract: The 190-kDa phosphoglycoprotein multidrug resistance protein 1 (MRP1) (ABCC1) confers resistance to a broad spectrum of anticancer drugs and also actively transports certain xenobiotics with reduced glutathione (GSH) (cotransport) as well as conjugated organic anions such as leukotriene C(4) (LTC(4)). In the present study, we have investigated a series of bioflavonoids for their ability to influence different aspects of MRP1 function. Most flavonoids inhibited MRP1-mediated LTC(4) transport in membrane vesicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
183
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(204 citation statements)
references
References 40 publications
20
183
1
Order By: Relevance
“…Human MRP3 plasmid (pcNDA3.1(2)-MRP3) and MRP4 plasmid (pcDNA3.1(2)-MRP4) were kindly provided by Dr. Susan Cole (Queen's University, Kingston, ON, Canada) and Dr. Dietrich Keppler (German Cancer Research Center, Heidelberg, Germany), respectively. Transiently transfected human embryonic kidney cells (HEK293T) were generated and membrane vesicles were prepared as described previously (Leslie et al, 2001). Transport experiments were carried out by a rapid filtration assay as described previously (Ghibellini et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Human MRP3 plasmid (pcNDA3.1(2)-MRP3) and MRP4 plasmid (pcDNA3.1(2)-MRP4) were kindly provided by Dr. Susan Cole (Queen's University, Kingston, ON, Canada) and Dr. Dietrich Keppler (German Cancer Research Center, Heidelberg, Germany), respectively. Transiently transfected human embryonic kidney cells (HEK293T) were generated and membrane vesicles were prepared as described previously (Leslie et al, 2001). Transport experiments were carried out by a rapid filtration assay as described previously (Ghibellini et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…-enriched membrane vesicle proteins were photolabeled with 8-azido-[␣-32 P]ATP essentially as described (46,47). Briefly, membrane vesicles (20 g) were dispersed in 20 l of transport buffer containing 5 mM MgCl 2 and 5 M 8-azido-[␣-32 P]ATP (1 Ci).…”
Section: Photolabeling Of Mrp1 By 8-azido-[␣-32 P]atp-mrp1mentioning
confidence: 99%
“…GSH transport was measured in the presence of apigenin (30 M), which previous studies have shown markedly enhances the uptake of this tripeptide by MRP1, thereby allowing more accurate quantitation (13,47). Relative to wild-type MRP1, GSH uptake by six of the nine MSD2 Pro mutants (P323A, P343A, P448A, P478A, P557A, and P595A) was substantially reduced (60 -93%), whereas GSH uptake levels by the P359A, P464A, and P600A mutants were comparable with wild-type MRP1 (Table II).…”
Section: Expression Levels and Transport Activities Of Mrp1 Mutants Cmentioning
confidence: 99%
“…For example, one of the most intensively investigated flavonoids, quercetin, is often just used as the aglycone in cell culture systems and interesting biological activities such as modulation of the multidrug-resistance protein [118], induction of apoptosis [168], inhibition of the expression of nitric oxide synthase and cyclooxygenase [162], protection against oxidative stress [88] and modulation of the calcium homeostasis [209] have been reported. However, in plants and, therefore, also in all plant-derived foods and beverages, quercetin is always present in a glycosylated form which completely alters its bioactivity.…”
Section: Flavonoids: Neuroprotective Agents In Vivo and In Vitro?mentioning
confidence: 99%